Topology design and kinematic optimization of cyclical 5-DoF parallel manipulator with proper constrained limb. (16th February 2017) - Wang, Panfeng; Huo, Xinming; Wang, Zhe
Abstract: This paper proposes topology design and kinematic optimization of cyclical 5-degree-of-freedom (DoF) parallel manipulator with proper constrained limb. Firstly, a type of cyclical 5-DoF parallel manipulators with proper constrained limb is proposed by analyzing DoF of the proper constrained limb within workspace. Exampled by a cyclical 5-DoF parallel manipulator with the topology 4-UP S&1-RP S, its motion mapping model is formulated. By taking the reciprocal product of a wrench on a twist as the generalized virtual power, the local and global kinematic performance indices are provided. Then, on the basis of the actuated and constrained singularity analysis of the 4-UP S&1-RP S parallel manipulator within the position and pose workspace, the topology design of the manipulator without singularity is carried out, and its reachable and prescribed workspaces are obtained. Finally, by maximizing the global kinematic performance index and subjecting to a set of appropriate constraint conditions, the kinematic optimal design of the 4-UP S&1-RP S parallel manipulator is carried out utilizing the genetic algorithm of MATLAB optimization toolbox. Abstract :